Racial/ethnic differences in clusters of adverse childhood experiences and associations with adolescent mental health - Xiaoyan Zhang; Shannon M. Monnat (Elsevier, 2022)
Childhood adversity is a well-established risk factor for mental health problems during adolescence. Using data from the Fragile Families and Child Wellbeing Study and latent class analysis (LCA), we examined patterns of exposure to ten adverse childhood experiences (ACEs), including socioeconomic adversity, among non-Hispanic (NH) White, NH Black, and Hispanic 9 year olds and determined associations between membership in ACE exposure "classes" and depression and anxiety scores at age 15 (N = 2849). Parental separation/divorce, economic hardship, and paternal incarceration were the most common ACEs. ACE prevalence was significantly higher among Blacks and Hispanics. ACEs clustered into four classes for Whites and Hispanics and three classes for Blacks. Over half of Whites were classified in the 'Low Adversity' class. Conversely, most Black and Hispanic adolescents were classified in the 'High Socioeconomic Adversity and Paternal Incarceration' class, characterized by above average probabilities of experiencing family economic hardship, parental separation/divorce, low maternal education, and paternal incarceration. A small share of adolescents in all three racial/ethnic groups were in the 'High Global Adversity' class, characterized by high probability of exposure to most ACEs, including physical and psychological abuse. Finally, ACE class membership was differentially associated with anxiety and depression across the three racial/ethnic groups, with generally larger differences in mental health scores across ACE groups for Whites than for Blacks and Hispanics. Our findings suggest that studies on the associations between ACEs and health outcomes that do not include childhood economic adversity risk underestimating the role of ACEs on mental health among racial/ethnic minorities. Moreover, different patterns of ACE exposure are differentially linked to anxiety and depression, and ACE group membership differences in anxiety and depression vary by racial/ethnic group. Findings suggest the need for racially tailored prevention and intervention strategies.